Unanchored Ubiquitin Chains, Revisited - Blount, Jessica R.; Johnson, Sean L.; Todi, Sokol V. (Frontiers in Cell and Developmental Biology, 2020)
The small modifier protein, ubiquitin, holds a special place in eukaryotic biology because of its myriad post-translational effects that control normal cellular processes and are implicated in various diseases. By being covalently conjugated onto other proteins, ubiquitin changes their interaction landscape − fostering new interactions as well as inhibiting others − and ultimately deciding the fate of its substrates and controlling pathways that span most cell physiology. Ubiquitin can be at-tached onto other proteins as a monomer or as a poly-ubiquitin chain of diverse structural topolo-gies. Among the types of poly-ubiquitin species generated are ones detached from another sub-strate − comprising solely ubiquitin as their constituent − referred to as unanchored, or free chains. Considered to be toxic byproducts, these species have recently emerged to have specific physiolog-ical functions in immune pathways and during cell stress. Free chains also do not appear to be det-rimental to multi-cellular organisms; they can be active members of the ubiquitination process, ra-ther than corollary species awaiting disassembly into mono-ubiquitin. Here, we summarize past and recent studies on unanchored ubiquitin chains, paying special attention to their emerging roles as second messengers in several signaling pathways. These investigations paint complex and flexi-ble outcomes for free ubiquitin chains, and present a revised model of unanchored poly-ubiquitin biology that is in need of additional investigation.